Olfactory deficits and sleep disturbances in Parkinson's disease: a case–control survey. Issue 7 (1st July 2003) - Henderson, J M; Lu, Y; Wang, S; Cartwright, H; Halliday, G M
Abstract : Background: Olfactory and sleep disturbances are common in Parkinson's disease, and may be early disease indicators. Objective: To obtain information about olfactory and sleep deficits preceding the onset of motor symptoms in Parkinson's disease. Subjects: 38 community dwelling patients with Parkinson's disease (73% response rate) and 32 age matched controls (60% response rate). Methods: Using a questionnaire survey, the frequencies, timing, and relations between olfactory and sleep disturbances, drug treatment, mood, and motor deficits in Parkinson's disease were compared with those in age matched controls. Reliability of information was validated by informant interview in 9% of the sample. Interdependency of factors was assessed using Fisher's fourfold table test, and differences between populations were analysed using χ 2 and unpaired t tests. Results: Microsmia was reported by 26 patients (68%) (and only one control), on average within a year of the diagnosis of Parkinson's disease. More patients than controls had excessive daytime somnolence (45% v 6%), restless legs (50% v 19%), and abnormal movements during sleep (34% v 0%), which generally occurred three to five years after diagnosis and were independent of mood disorders and drug treatment. Conclusions: Many patients with Parkinson's disease have microsmia at the onset of motor deficits, but some sleep disorders are a subsequent occurrence.